Involvement of the European Medicines Agency in multi-stakeholder regulatory science research projects: experiences of staff members and project coordinators - Saesen, Robbe; Machado, Matilde; Crifo, Bianca; Liu, Lifang; de Vries, Corinne; Herold, Ralf; Llinares Garcia, Jordi; Huys, Isabelle (Frontiers in Medicine, 2023)
Background: The European Medicines Agency (EMA) interacts with many different stakeholders involved in the development of drugs, including academic researchers. In recent years, EMA has collaborated more closely with academia, inter alia by taking part in external research projects such as those set up under the Horizon 2020 program in general and the Innovative Medicines Initiative in particular. The aim of this study was to evaluate the perceived added value of EMA’s involvement in these projects, both from the perspective of the Agency’s participating Scientific Officers and of the coordinators of the consortia that undertook them. Methods: Semi-structured interviews were conducted with the coordinators of 21 ongoing or recently finalized projects in which EMA has participated, as well as with the Agency experts contributing to them. Results: In total, 40 individuals were interviewed, of whom 23 were project coordinators and 17 were EMA staff members. While most of the projects were reported to suffer from delays due to the SARS-CoV-2 pandemic, the consortia adapted to the circumstances and their members still expected to deliver on their objectives. EMA’s input into the projects ranged from providing guidance by reviewing documents and attending meetings to creating project materials and disseminating them. The frequency of communication between EMA and the consortia varied widely. The projects generated a diverse set of outputs, which encompassed new or improved medicinal products, methodological standards, research infrastructures and educational tools. All of the coordinators expressed that EMA’s contributions to their projects had increased the scientific relevance of their consortium’s work, and the EMA experts found that the knowledge and the deliverables produced by the projects were valuable, taking into consideration the time they had invested into them. In addition, interviewees highlighted some actions which could be taken to increase the regulatory significance of the project outcomes. Conclusion: EMA’s engagement in external research projects benefits the consortia conducting them and supports the Agency’s mission to foster scientific excellence and advance regulatory science.